A Machine Boosting Energy into the Universe - Praepipatmongkol, Chanon Kenji; Iskandar, Syaheedah (Singapore Art Museum, 2022)
Texts: Chanon Kenji Praepipatmongkol and Syaheedah Iskandar, Alex Quicho, Akapol Op Sudasna, Alex Gvojic, Chomwan Weeraworawit
English
Keywords: N4390-5098 Visual Arts. Exhibitions